(untitled) - Taylor-Ide, Daniel (San Francisco, 1995)
Beginning with a search for Yeti, the abominable snowman, or Big-Foot, Taylor-Ide gradually came to believe that what's most important in the Himalayas is to protect the rare environment so that whatever lives there may continue.
Keywords: Natural history,Lịch sử tự nhiên; Nepal,Nepal